2014
DOI: 10.2215/cjn.02500314
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Mortality of ESRD Patients with Lupus by Initial Dialysis Modality

Abstract: Background and objectives Little is known regarding whether mortality among ESRD patients with SLE differs between those initiating with peritoneal dialysis (PD) versus hemodialysis (HD). This study compared the mortality risk of ESRD patients with SLE initiating with PD versus HD after matching their baseline sociodemographic and clinical factors.Design, setting, participants, & measurements Of 11,023 ESRD patients with SLE initiating dialysis with PD or HD between 1995 and 2006 with complete records in the U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
1

Year Published

2015
2015
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 11 publications
1
19
0
1
Order By: Relevance
“…PD treatment offers numerous advantages [ 22 , 23 ], however only 7 to 10% of end-stage renal disease patients are treated with PD [ 2 ]. This reflects, at least in part, the clinicians’ fear of technical failure [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…PD treatment offers numerous advantages [ 22 , 23 ], however only 7 to 10% of end-stage renal disease patients are treated with PD [ 2 ]. This reflects, at least in part, the clinicians’ fear of technical failure [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…From 16 ultimately eligible studies, 15,636 patients were diagnosed to have LN-ESRD prior to renal transplantation. Of 15,636 patients, 4616 were on hemodialysis and 2089 were on peritoneal dialysis, 280 directly underwent kidney transplantation, 8319 were eliminated in 1 study [24] after matching participants utilizing propensity scores by the primary author and for 332 participants details were not reported [16]. All 16 studies reported 1 or more outcomes of interest.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…A total of 5 studies were conducted in Taiwan [19,[21][22][23]38], 3 in the United States of America (USA) [20,24,31], 1 in China [32], UK, Australia, France, Croatia, Brazil, and 2 in South Korea [13,36]. All studies were retrospectively conducted studies while 2 [22,38] were prospectively conducted.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Son aceptables tanto hemodiálisis como peritoneodiálisis y trasplante renal 32,33 . En lupus activos con inmunosupresión se ha observado mayor incidencia de infecciones con peritoneodiálisis que con hemodiálisis, favoreciendo esta última con accesos vasculares adecuados.…”
Section: ¿Qué Tipo De Trr Pueden Recibir Los Pacientes Con Nl?unclassified